Epidemiology, biostatistics, and preventive medicine - Jekel, James F; Elmore, Joann G; Katz, David L (W.B. Saunders, 1996)
Yale University, New Haven, CT. Synopsis for medical students relating epidemiology, biostatistics, and preventive medicine to clinical practice, research, and public policy. For course or exam review. DNLM: Epidemiologic Methods.
Keywords: epidemiologie; veřejné zdravotnictví